O tango espetáculo na região binacional do Brasil com a Argentina - Oliveira, Daiane Glaucia de (2018)
The present work presents a reflection on how the Tango Show is built in the Brazilian Binational Frontier with Argentina and its relation as a cultural product inserted in the local tourism, contextualizing the Tango as Artistic Manifestation and Intangible Cultural Heritage of Humanity. Thus, the tango was presented in its construction process according to the history of dance and the contributions of the other genres that make it up or contributed in its formation and maintenance process. Among the objectives that permeate this research, reference is made to the transmission between generations and through the shows that come from the binational region, constituted by different borders, as well as characteristics that promote the feeling of belonging and identity. The tango show or scenario, present at the frontier is also considered a good and a resource for local tourism, suggesting to this investigation to note how companies use this medium within the handling and structure of the shows offered to tourists. For this result, we used bibliographic methodological contributions, supported by authors who investigated the dance, such as Hélio Fernandes (2000), Luis Labraña (2000), Hernán Morél (2009), Antonio Perna (2011) and Florencia Garramuño (2009). In addition, as a methodological process of data collection, the observation technique was used, through the researcher's perspective as a professional in the area of ballroom dancing, and professionally involved in a particular moment of the career, with some of the companies mentioned. Another resource used was the semi-structured interviews directed at companies that have tango in regular shows directed to tourists. From the problematizations, objectives and through the methods and methodologies, it was looked for to answer the questions that brought to this research being based on references from the approaches of authors like Herib